METHOD DEVELOPMENT& SIMULTANEOUS ESTIMATION OF METFORMIN HYDROCHLORIDE AND REPAGLINIDE IN TABLET DOSAGE FORM - Jain, Madhavi; Sharma, Ami; Soni, Love Kumar; Kabra, Mahaveer (Asian Journal of Pharmaceutical Research and Development, 2013)
Development and Validation of RP-HPLC Method for Simultaneous Estimation of MET and RPG in Tablet Dosage Form was performed by using LC system consists of pump (Shimadzu LC 10AT VP) with universal loop injector (Rheodyne 7725 i) of injection capacity 20 µL. Detector consists of Photodiode Array Detector (PDA) SPD-10 AVP UVVisible detector, for separation column used was Chromatopak C18 (5µm×250mm×4.6mm i.d). For quantitative estimation of MET and RPG, mobile phase used was acetonitrile : water in the volume of 90 : 20 v/v with the flow rate of 1.0ml/ min was confirmed by considering the resolution between both the peaks. Detection wavelength 223nm was selected as both the analyte absorbed well and at this particular wavelength neither any interference from the mobile phase nor any baseline disturbance appeared. Validation reveals the method is specific,rapid,accurate,precise,reliable and reproducible. The high recovery and low coefficients of variation confirm the suitability of the method of simultaneous analysis of the two drugs in tablets.